The comparative study of clinical efficacy and safety of baclofen vs tolperisone in spasticity caused by spinal cord injury - Dejun Luo; Guoyong Wu; Yong Ji; Zhaoyao Zhang; Fayou He; Xiaping Mou; Qingmao Zhu; Bo Yang (Elsevier, 2017)
In the present study we compared the clinical efficacy and safety of baclofen vs tolperisone in spasticity caused by spinal cord injury. A total of 150 patients were enrolled in the present study and were divided into two groups with 75 patients in each group, receiving baclofen or tolperisone, respectively. We used Modified Ashworth Scale, Medical research council scale, Barthel Index, and Coefficient of efficacy to measure clinical efficacy. After 6-week treatment, both groups demonstrated significant improvement in muscle tone, muscle strength and functional outcome (Group I, 1.55 ± 0.053, 2.79 ± 0.032, 59.31 ± 1.32; Group II, 1.57 ± 0.053, 3.04 ± 0.032, 73 ± 1.32 respectively). There was no significant difference regarding improvement in muscle tone and muscle strength between the two groups (Group I, 1.055 ± 0.053 vs Group II, 1.57 ± 0.053; Group I, 2.79 ± 0.032 vs Group II, 3.04 ± 0.032, p > 0.05). However, the improvement in functional outcomes was greater in group II as compared to that in group I (Group I, 59.31 ± 1.32 vs Group II, 73 ± 1.32, p < 0.05). In addition, overall efficacy coefficient was greater for group II as compared to group I (Group I, 3.6 vs Group II, 2.3, p < 0.05). Group I had more side effects compared to Group II. Compared to baclofen, tolperisone offers greater improvement in activities of daily living compared to baclofen. Keywords: Spinal cord injury, Spasticity, Baclofen, Tolperisone